2023
DOI: 10.1002/cbic.202300095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epitranscriptomic RNA Modifications on the Catalytic Activity of the SARS‐CoV‐2 Replication Complex**

Abstract: SARS-CoV-2 causes individualized symptoms. Many reasons have been given. We propose that an individual's epitranscriptomic system could be responsible as well. The viral RNA genome can be subject to epitranscriptomic modifications, the modifications can be different for different individuals, and thus epitranscriptomics can affect many events including RNA replication differently. In this context, we studied the effects of modifications including pseudouridine (Ψ), 5methylcytosine (m 5 C), N 6 -methyladenosine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…From the above experiments and the data we published earlier regarding inhibition of SARS-CoV-2 RdRp by m 1 A in RNA template [8], it is clear that m 1 ATP based prodrugs may be investigated for the treatment of COVID-19. The reason is that once m 1 ATP is formed from a prodrug in SARS-CoV-2 infected cells, the viral RdRp could incorporate m 1 A into its RNA genome.…”
Section: Preprintsmentioning
confidence: 56%
See 3 more Smart Citations
“…From the above experiments and the data we published earlier regarding inhibition of SARS-CoV-2 RdRp by m 1 A in RNA template [8], it is clear that m 1 ATP based prodrugs may be investigated for the treatment of COVID-19. The reason is that once m 1 ATP is formed from a prodrug in SARS-CoV-2 infected cells, the viral RdRp could incorporate m 1 A into its RNA genome.…”
Section: Preprintsmentioning
confidence: 56%
“…Besides m 1 A, there are over 300 epitranscriptomic RNA modifications [12][13][14]. Among them, we have found that m 3 C in RNA template does not inhibit SARS-CoV-2 RdRp [8], which was surprising considering that m 1 A inhibits the RdRp and both m 1 A and m 3 C disrupt canonical base pairing. However, even though m 3 C does not inhibit RdRp, it is unlikely that the nucleotide incorporated across it is precisely G due to G-C base pair disruption by the modification.…”
Section: Preprintsmentioning
confidence: 98%
See 2 more Smart Citations
“…Viral infection has been shown to impact the expression levels of m 1 A writers and erasers on host mRNA, and some of them may have proviral effects ( 203 ). Intriguingly, upregulated m 1 A on host RNA inhibits the activity of the replication complex of SARS-COV-2 and thus achieves an antiviral effect, an effect that does not appear to be related to the steric hindrance caused by m 1 A ( 233 ). As for the impact on immune cells, research on m 1 A has mainly focused on cancer, such as its influence on immune cell infiltration ( 111 ).…”
Section: Non-m 6 a Rna Modifications In Antiviral ...mentioning
confidence: 99%